심신장애자의 구강보건 실태 및 상대구강보건의료수요에 대한 조사연구 - 유상현 (연세대학교 보건대학원, 1987)
[한글] 심신장애자들의 구강보건 및 치과의료에 대해서 최근 치의학계의 관심도가 증가하고 있는 가운데, 실질적인 구강보건사업의 계획을 위하여 그 실태를 조사하는 것은 큰 의미를 갖는다. 저자는 이에 착안하여 심신장애자들의 합리적이고도 활용 가능한 구강 보건관리 계획을 수립하는 데에 필요한 기초 자료를 마련할 목적으로 본 연구를 실시하게 되었다. 연구대상은 1986년 현재 서울특별시에 존재하는 17개 재활학교 및 재활원에 통학하거나 수용되어 있는 심신장애자들 중 남녀 698명을 층화표본추출하였다. 연구방법은 세계보건기구가 권장하는 조사방법과 기준을 따랐으며 조사된 자료를 전산기로 집계하여 처리분석 하였다. 그 결과를 요약하면 다음과 같다. 1. 장애자들의 연성부착물부착도가 전체적으로 높아, 구강위생상태가 매우 불량하였고, 유치열기에는 치석이 부착되어 있지 않았으나, 혼합치열기 이상에서 치석부착도는 고연령층에서 높게 나타났으며, 영구치열기의 지체·정박군에서 가장 높게 나타났다. 2. 치은염은 유치열기 에서는 관찰되지 않았으며, 지체·정박군의 영구치열기에서 50%로 가장 높은 유병율을 보였다. 3. 치주병은 혼합치열기 이하에서는 거의 발생하지 많았으며 정박군의 영구치열기에서만 18.3%로 관찰되었다. 4. 심신장애자들의 연성부착물부착율, 치석부착율, 치은염유병율, 치주병유병율은 지체·정박군과 정박군에서 청각장애군보다 높게 나타났으며 이는 구강보건관리능력과 밀접한 관계가 있는 것으로 나타났다. 5. 장애자들의 치주처치수요는 고도의 치주치료보다는 단순한 구강보건관리교육 및 치면세마에의 수요가 구강보건학적 차원에서 시급합을 나타냈다. 6. 청각장애군에서는 치주처치수요에 대한 심각성이 관찰되지 않았다. 7. 치아우식경험율은 유치에 있어서는 장애유형간에 별차가 없었으나 영구치에 있어서는 구강관리 능력이 양호한 청각장애군에서 낮게 나타났다. 8. 치아처치수요는 충전대상에 있어서는 장애유형간에 별차가 없었으며 발거대상에 있어서는 청각장애 영구치열기에서 관찰되지 않았다. 9. 구강보건사업계획에 있어서, 치아우식증처치는 장애유형에 관계없이 계획되어야 하며, 치주처치는 지체·정박군과 정박군에서 우선적으로 계획되어야 한다고 생각된다. [영문] The purpose of this study was to review the available oral health care programs of the handicapped and to make any necessary recommendations for their improvement. 698 handicapped patients living in Seoul were examined during 1986. The following results were obtained: 1. Generally, the patient's oral hygiene was poor, and the older the patient the poorer the hygiene. 2. Intense gingivitis, while not observed in the deciduous dentition group, was noted in patients with permanent dentition who were mentally and physically handicapped. 3. Periodontitis was observed in a few cases in the mentally retarded, permanent dentition group. 4. Better oral hygiene was displayed in the hearing impaired then in any other handicapped group. This implied that there is a relationship between oral health and one's own ability to provide the proper care. 5. Those patients with periodontal disease were given simple oral, hygiene care, rather than more extensive procedures. 6. The hearing impaired group did not require periodontal treatment. 7. The 3 handicapped groups displayed no significant differences with regard to the incidence of dental carries in the deciduous teeth. The hearing impaired group had a lower incidence of caries in the permanent dentition. 8. Their was no significant difference in the need for restorations among the groups : the hearing impaired group did net require any extractions of permanent teeth. 9. When oral health care programs are planned, one must consider that there are no differences in the incidence of dental cartes among the handicapped group, but there are differences in the incidence of periodontal disease. A good oral hygiene routine and periodontal therapy should be instituted for the physically and dentally handicapped as soon as possible.
보건학과/석사